2019
DOI: 10.15184/aqy.2019.80
|View full text |Cite
|
Sign up to set email alerts
|

Meet the Vikings: for real!

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…At the National Museum of Finland's permanent exhibition between 1995 and 2016, the grave was used as evidence of female leaders in the past (Erä-Esko et al, 1995: 45). In popular discussions and contexts, for example history forums on the internet, international sword replica shops, and even in the controversial ‘Meet the Viking’ exhibition at the National Museum of Denmark (see Pentz et al, 2019; Sindbæk, 2019), the decorated bronze-hilted sword allegedly found in the Suontaka burial is presented as a female warrior's weapon.
Figure 1.Location of the Häme (Tavastia) region in Finland, with Suontaka marked with a red dot.
…”
Section: Introductionmentioning
confidence: 99%
“…At the National Museum of Finland's permanent exhibition between 1995 and 2016, the grave was used as evidence of female leaders in the past (Erä-Esko et al, 1995: 45). In popular discussions and contexts, for example history forums on the internet, international sword replica shops, and even in the controversial ‘Meet the Viking’ exhibition at the National Museum of Denmark (see Pentz et al, 2019; Sindbæk, 2019), the decorated bronze-hilted sword allegedly found in the Suontaka burial is presented as a female warrior's weapon.
Figure 1.Location of the Häme (Tavastia) region in Finland, with Suontaka marked with a red dot.
…”
Section: Introductionmentioning
confidence: 99%
“…Lyngvild's striking designs, his ability to engage the audience, and his deliberate challenges to the cultural establishment, were a success with the public. Yet the result of a rushed process and somewhat faltering communication left aims and frames unclear and caused mixed reactions (Sindbaek 2018;Pentz et al 2019). For the new permanent gallery, the museum has clearly aimed to steer a different course.…”
mentioning
confidence: 99%
“…Although this may come across as an abdication of responsibility on the part of the museum team, there is perhaps more to be said for what may have been a deliberate choice to create a depopulated vision of a Viking world. The JOR-VIK Viking Centre is still evoked as the first to attempt a museum-based reconstruction of Viking people in authentic surroundings, an enterprise in which it has been judged successful and which is presented as the justification for subsequent efforts by others to do the same (Pentz et al 2019); a closer look at JORVIK's 40 years of reconstructing, performing and displaying Vikings, however, reveals how its Vikings have always drawn fire (Tuckley 2020), which is perhaps only to be expected where an historical brand, in its popular iterations, has been so mired in confrontational and problematic representations of gender, race and violence.…”
mentioning
confidence: 99%
“…It seems that for those who take an interest in these matters, there is something essentially unsatisfactory about what we might term 'public Vikings'. This may be behind the choice to avoid them altogether at the Swedish History Museum, or to revert to the safer option of celebrity Vikings such as Harald Bluetooth at the National Museum in Copenhagen (where the 2018 Meet the Vikings exhibition had taken daring steps to imagine and picture larger-than-life Viking characters by working with reenactors, tolerating or celebrating the anachronisms in the results; Pentz et al 2019). Wherever they occur, public Vikings seem caught somewhere between (at least) two irreconcilable and competing sets of demands.…”
mentioning
confidence: 99%